Diagnostic value of immunological skin tests in children with tuberculosis - A. G. Smetanin; Ya. A. Dauletova; S. L. Leonov (Туберкулез и болезни лёгких)
The paper gives the results of an analysis of intracutaneous Mantoux tuberculin tests with 2 TU, 1 TU, 0.1 TU, and 0.01 TU PPD-L and intracutaneous Diaskintest using recombinant tuberculosis allergen in the standard dilution in 63 children with tuberculosis. A moderate correlation was found between the results of the above tests. There was the highest sensitivity of the immune system to the administration of 0.01 TU PPD-L (0.0006 µg). A high specific responsiveness as a hyperergic reaction was established when recombinant tuberculosis allergen was used in standard dilution (0.2 µg). There were moderately intensive and weakly positive reactions (10-14- and 5-9-mm infiltrates) to the administration of 2 TU (0.12 µg) of tuberculin in the skin test. The tuberculin skin test with 0.01 TU PPD-L was ascertained to be of more significant diagnostic value than the Diaskintest using recombinant tuberculosis allergen in standard dilution.